Petrogenesis of late carboniferous adakitic dikes and granodiorites in the Chinese Altai, NW China: Implications for lower crustal melting and slab roll-back - Shuaiyu Guo; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Yunchuan Zeng; Zaili Tao; Fan Yang; Jianjun Zhang; Tao Wang; Wenjiao Xiao (Lithos, 2026)

Rapid recycling of sediment-derived granites in accretionary orogens: Implications from the Alataw Mountains, NW China - Jiyuan Yin; He Huang; Ilya Bindeman; Chiara Maria Petrone; Mike Fowler; Andrew C. Kerr; Zaili Tao; Tao Wang; Min Sun; Guochun Zhao; Wenjiao Xiao (Chemical Geology, 2026)

Microplastic dynamics and land contamination in deltaic environments- A systematic review of current understanding and knowledge gaps - Md Atikul Islam; Mohammad A. Hoque; Fay Couceiro; Mike Fowler (Environmental Pollution, 2026)

Geochemical, thermodynamic and Li isotope constraints on the genesis of rare-metal pegmatites: Implications for crustal Li cycling - Qing Du; Jiyuan Yin; Wenjiao Xiao; Tao Wang; Mike Fowler; Zhiyong Zhu; Zaili Tao; Guibin Zhang; Min Sun; Guochun Zhao (Global and Planetary Change, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Cretaceous to Cenozoic Magmatic and Crustal Evolution of the Pamir-West Kunlun Orogenic Belt - Fan Yang; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Zaili Tao (Journal of Earth Science, 2025)

Coeval TTG and sanukitoid magmatism during the Rhyacian tectonic evolution of the Juiz de Fora Complex (São Francisco Paleocontinent, SE-Brazil) - Sandro Mauri; Monica Heilbron; Henrique Bruno; Samuel Bersan; Rasec Almeida; Rodson de Abreu Marques; Syro Lacerda; Ariadne Marra de Souza; Gabriel Paravidini; Carla Neto; Cláudio de Morisson Valeriano; Glenn Chapman; et al. (Precambrian Research, 2024)

Barium-Mg isotopes in high Ba-Sr granites record a melt-metasomatized mantle source and crustal growth - Ren-Zhi Zhu; Mike Fowler; Fang Huang; Emilie Bruand; Xiao-Jun Wang; Li-Hui Chen; Craig Storey; Jiyuan Yin; Shaocong Lai (Geochimica et Cosmochimica Acta, 2024)

Maturation from oceanic arcs to continental crust: Insights from Paleozoic magmatism in West Junggar, NW China - Jiyuan Yin; Wenjiao Xiao; Tao Wang; Mike Fowler; Andrew C. Kerr; Min Sun; Rob Strachan; He Huang; Ji'en Zhang; Wen Chen; Zaili Tao (Earth-Science Reviews, 2024)

Rhyacian-Orosirian transitional arc-collisional magmatism in the Archean Piedade Microcontinent, southern São Francisco Paleocontinent, Brazil - Mariana Carvalho; Henrique Bruno; Samuel Bersan; Craig Storey; Catherine Mottram; Glenn Chapman; Mike Fowler; Claudio Valeriano; Cristiano Lana; Carla Neto; Monica Heilbron (Precambrian Research, 2024)

A microcosm of modern crust formation: Evidence from zircon ages, Hf O and Nd Sr isotopes and bulk geochemistry of the Menglian Batholith, SE Tibet - Ren-Zhi Zhu; Shao-Cong Lai; Mike Fowler; Jin-Cheng Xie; Sarah M. Glynn (Chemical Geology, 2023)

High-K calc-alkaline to shoshonitic intrusions in SE Tibet: implications for metasomatized lithospheric mantle beneath an active continental margin - Ren-Zhi Zhu; Ewa Słaby; Shao-Cong Lai; Li-Hui Chen; Jiangfeng Qin; Chao Zhang; Shaowei Zhao; Fangyi Zhang; Wen-hang Liu; Mike Fowler (Contributions to Mineralogy and Petrology, 2021)

Recruitment and facilitation in Pinus hartwegii, a Mexican alpine treeline ecotone, with potential responses to climate warming - Claudia C. Astudillo-Sánchez; Mike S. Fowler; José Villanueva-Díaz; Angel R. Endara-Agramont; Leroy Soria-Díaz (Trees, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Functional diversity of predators and parasitoids does not explain aphid biocontrol efficiency - Sanaa N. Alhadidi; Mike S. Fowler; John N. Griffin (BioControl, 2019)

The colour of environmental fluctuations associated with terrestrial animal population dynamics - David Gilljam; Jonas Knape; Andreas Lindén; Marianne Mugabo; Steven M. Sait; Mike S. Fowler (Global Ecology and Biogeography, 2019)
Aim The temporal structure (colour) of environmental variation influences population fluctuations, extinction risk and community stability. However, it is unclear whether environmental covariates linked to population fluctuations are distinguishable from a purely random process (white noise). We aimed to estimate colour coefficients and relative support for three models commonly representing coloured stochastic processes, in environmental series linked to terrestrial animal population fluctuations. Location North America and Eurasia. Time period 1901–2002. Major taxa studied Birds, insects and mammals. Methods We analysed multiple abiotic environmental covariates, comparing point estimates and confidence intervals of temporal structure in competing models fitted using white noise, autoregressive [AR(1)] and 1/ f processes in the time domain and the frequency domain (where time series were analysed after decomposition into different sinusoidal frequencies and their relative powers). All animal time series were sampled annually for ≤ 50 years, potentially inflating type II errors. We also considered 101‐year series of matched environmental covariates, performing a statistical power analysis evaluating our ability to draw robust conclusions. Results Temperature‐related variables were associated with the largest fraction of population fluctuations. Ninety‐three per cent of shorter environmental series were indistinguishable from white noise, limited by time‐series length and associated with wide confidence intervals. The longer environmental series analysed in the time domain offered sufficiently high statistical power to identify correctly colour estimates ≥ |0.27|, indicating that 20% of series were best described by a slightly reddened noise process. Main conclusions Focusing on the short time‐scales typically available for ecologists, most environmental variables associated with terrestrial animal population fluctuations are best characterized by white noise processes, although type II errors are common. The correct detection of intermediately coloured noise with power 0.8 requires ≥ 16 data points in the time domain or ≥ 47 points in the frequency domain. Over longer time‐scales, where type II errors are less likely, one‐fifth of populations are associated with coloured (often reddened) variables.

Optimising physiochemical control of invasive Japanese knotweed - Daniel Jones; Gareth Bruce; Mike S. Fowler; Rhyan Law-Cooper; Ian Graham; Alan Abel; F. Alayne Street-Perrott; Daniel Eastwood (Biological Invasions, 2018)
Japanese knotweed, Fallopia japonica var. japonica , causes significant disruption to natural and managed habitats, and provides a model for the control of invasive rhizome-forming species. The socioeconomic impacts of the management of, or failure to manage, Japanese knotweed are enormous, annually costing hundreds of millions of pounds sterling (GBP£) in the UK alone. Our study describes the most extensive field-based assessment of F. japonica control treatments undertaken, testing the largest number of physical and/or chemical control treatments (19 in total) in replicated 225 m 2 plots over 3 years. Treatments focused on phenology, resource allocation and rhizome source–sink relationships to reduce the ecological impacts of controlling F. japonica . While no treatment completely eradicated F. japonica, a multiple-stage glyphosate-based treatment approach provided greatest control. Increasing herbicide dose did not improve knotweed control, but treatments that maximised glyphosate coverage, e.g., spraying versus stem injection, and exploited phenological changes in rhizome source–sink relationships caused the greatest reduction of basal cover and stem density after 3 years. When designing management strategies, effective control of F. japonica may be achieved by biannual (summer and autumn) foliar glyphosate applications at 2.16 kg AE ha −1 , or by annual application of glyphosate in autumn using stem injection at 65.00 kg AE ha −1 or foliar spray at 3.60 kg AE ha −1 . Addition of other herbicides or physical treatment methods does not improve control. This work demonstrates that considering phenology, resource allocation and rhizome source–sink relationships is critical for the control of invasive, rhizome forming species.

Natural enemy composition rather than richness determines pest suppression - Sanaa N. Alhadidi; John N. Griffin; Mike S. Fowler (BioControl, 2018)

Top-down and bottom-up control on cougar and its prey in a central Mexican natural reserve - Leroy Soria-Díaz; Mike S. Fowler; Octavio Monroy-Vilchis (European Journal of Wildlife Research, 2017)

Boom‐bust dynamics in biological invasions: towards an improved application of the concept - David L. Strayer; Carla M. D'Antonio; Franz Essl; Mike S. Fowler; Juergen Geist; Sabine Hilt; Ivan Jarić; Klaus Jöhnk; Clive G. Jones; Xavier Lambin; Alexander W. Latzka; Jan Pergl; et al. (Ecology Letters, 2017)
Boom‐bust dynamics – the rise of a population to outbreak levels, followed by a dramatic decline – have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom‐bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom‐bust dynamics and provide specific suggestions for improving the application of the boom‐bust concept. Boom‐bust dynamics can arise from many causes, some closely associated with invasions, but others occurring across a wide range of ecological settings, especially when environmental conditions are changing rapidly. As a result, it is difficult to infer cause or predict future trajectories merely by observing the dynamic. We use tests with simulated data to show that a common metric for detecting and describing boom‐bust dynamics, decline from an observed peak to a subsequent trough, tends to severely overestimate the frequency and severity of busts, and should be used cautiously if at all. We review and test other metrics that are better suited to describe boom‐bust dynamics. Understanding the frequency and importance of boom‐bust dynamics requires empirical studies of large, representative, long‐term data sets that use clear definitions of boom‐bust, appropriate analytical methods, and careful interpretations.

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

Ecological and evolutionary implications of food subsidies from humans - Daniel Oro; Meritxell Genovart; Giacomo Tavecchia; Mike S. Fowler; Alejandro Martínez‐Abraín (Ecology Letters, 2013)
Human activities are the main current driver of global change. From hunter‐gatherers through to Neolithic societies–and particularly in contemporary industrialised countries–humans have (voluntarily or involuntarily) provided other animals with food, often with a high spatio‐temporal predictability. Nowadays, as much as 30–40% of all food produced in Earth is wasted. We argue here that predictable anthropogenic food subsidies ( PAFS ) provided historically by humans to animals has shaped many communities and ecosystems as we see them nowadays. PAFS improve individual fitness triggering population increases of opportunistic species, which may affect communities, food webs and ecosystems by altering processes such as competition, predator–prey interactions and nutrient transfer between biotopes and ecosystems. We also show that PAFS decrease temporal population variability, increase resilience of opportunistic species and reduce community diversity. Recent environmental policies, such as the regulation of dumps or the ban of fishing discards, constitute natural experiments that should improve our understanding of the role of food supply in a range of ecological and evolutionary processes at the ecosystem level. Comparison of subsidised and non‐subsidised ecosystems can help predict changes in diversity and the related ecosystem services that have suffered the impact of other global change agents.

Species dynamics alter community diversity–biomass stability relationships - Mike S. Fowler; Jouni Laakso; Veijo Kaitala; Lasse Ruokolainen; Esa Ranta (Ecology Letters, 2012)
The relationship between community diversity and biomass variability remains a crucial ecological topic, with positive, negative and neutral diversity–stability relationships reported from empirical studies. Theory highlights the relative importance of Species–Species or Species–Environment interactions in driving diversity–stability patterns. Much previous work is based on an assumption of identical (stable) species‐level dynamics. We studied ecosystem models incorporating stable, cyclic and more complex species‐level dynamics, with either linear or non‐linear density dependence, within a locally stable community framework. Species composition varies with increasing diversity, interacting with the correlation of species' environmental responses to drive either positive or negative diversity–stability patterns, which theory based on communities with only stable species‐level dynamics fails to predict. Including different dynamics points to new mechanisms that drive the full range of diversity–biomass stability relationships in empirical systems where a wider range of dynamical behaviours are important.

Stock discrimination of Southern Garfish (Hyporhamphus melanochir) by stable isotope ratio analysis of otolith aragonite - Mike A. Steer; Galen P. Halverson; Anthony J. Fowler; Bronwyn M. Gillanders (Environmental Biology of Fishes, 2010)

When can we distinguish between neutral and non‐neutral processes in community dynamics under ecological drift? - Lasse Ruokolainen; Esa Ranta; Veijo Kaitala; Mike S. Fowler (Ecology Letters, 2009)
Determining whether the composition of ecological communities (species presence and abundance), can be predicted from species demographic traits, rather than being a result of neutral drift, is a key ecological question. Here we compare the similarity of community composition, from different community assembly models run under identical environmental conditions, where interspecific competition is assumed to be either neutral or niche‐based. In both cases, species colonize a focal patch from a network of neighbouring patches in a metacommunity. We highlight the circumstances (rate and spatial scale of dispersal, and the relative importance of ecological drift) where commonly used community similarity metrics or species rank–abundance relationships are likely to give similar results, regardless of the underlying processes (neutral or non‐neural) driving species’ dynamics. As drift becomes more important in driving species abundances, deterministic niche structure has a smaller influence. Our ability to discriminate between different underlying processes driving community organization depends on the relative importance of different drift processes that operate on different spatial scales.

Simple laboratory tests of ecological theories: What we can learn from them, and when we should be cautious - Mike S. Fowler; Lasse Ruokolainen (Journal of Biosciences, 2006)

Oxidative stress induced by lead, cadmium and arsenic mixtures: 30-day, 90-day, and 180-day drinking water studies in rats: An overview - Bruce A. Fowler; Margaret H. Whittaker; Mike Lipsky; Gensheng Wang; Xue-Qing Chen (BioMetals, 2004)

Influence of hydrologic exchange patterns on water chemistry and hyporheic invertebrate communities in three gravel‐bed rivers - Reece T. Fowler; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2002)
The influence of hydraulic exchange patterns on hyporheic water chemistry and invertebrate community composition was measured in three gravel‐bed rivers of southern Hawke's Bay, North Island, New Zealand. Based on patterns reported overseas we predict that down‐welling waters will be similar to surface waters in chemical characteristics and epigean animals will be more common in down‐welling waters than in up‐wellings, which would have a different chemical signature to the surface waters and a fauna dominated by hypogean invertebrates. Conductivity, pH, and temperature of hyporheic water were least like those of surface waters at up‐wellings in the groundwater‐fed Makaretu River. Only 6% of the invertebrate fauna of these up‐wellings comprised epigean animals. In contrast, in the groundwater‐recharging Tukituki and Waipawa Rivers, hyporheic water chemistry was similar to that of surface water in down‐wellings and 40% of the community comprised epigean animals by abundance. Significant increases (P 0.05) in species diversity and taxonomic richness was also identified in down‐welling zones compared with up‐wellings. Species diversity and taxonomic richness were lowest in up‐wellings in the Makaretu where hypogean animals dominated the hyporheic fauna. Species diversity and taxonomic richness were higher in down‐wellings than up‐wellings because more epigean taxa were present.